Optimising Energy Efficiency in Offshore Buildings: Supporting SDG 7 - Clean and Affordable Energy - Palippui, Habibi (Maritime Park: Journal of Maritime Technology and Society, 2024)
The offshore oil and gas sector faces significant challenges in reducing its carbon footprint while meeting global energy demand. Offshore structures consume up to 500 MW of energy per day. Despite the potential for 30-40% energy savings with efficiency technologies, only 25% of global platforms implement integrated energy management systems. This study aims to optimize energy efficiency in offshore structures to support SDG 7 - Affordable and Clean Energy. The study uses a multi-method approach, analyzing data from 10 offshore platforms, conducting energy modeling, and cost-benefit analysis. The results show variability in daily energy consumption (423.7 ± 32.5 MW) with key factors such as hydrocarbon production and environmental conditions. Energy efficiency technologies such as hybrid power generation systems and Integrated Energy Management Systems (SMET) show significant potential for savings. The optimization model shows a total potential energy savings of 37.2 ± 2.1%. Economic analysis using Monte Carlo simulations confirms the feasibility of investment with positive NPV for all evaluated technologies. SMET has the most favorable risk-return profile with a mean NPV of 5.8 ± 0.7 million USD. These findings provide important insights for operators and policymakers, emphasizing the importance of a holistic approach to energy management in offshore structures. Implementation of the proposed energy efficiency strategies can contribute significantly to climate change mitigation and the achievement of SDG 7.